Early detection of hearing loss: exploring risk-based hearing screening within a developing country context - Kanji, Amisha (My University, 2016)
Purpose: The main objective of the current study was to explore risk-based new-born hearing screening within a developing country by conducting early hearing detection in high-risk neonates within an academic hospital complex in Gauteng, South Africa. Specific objectives describing the case history factors and audio logical function in a group of high-risk determining the relationship between the case history factors and audio logical establishing the true-positive (TP) and true-negative (TN) results with different combinations of screening measures; establishing the percentage of TP and NT screening results in the total sample; and exploring the factors associated with follow-up return rate for hearing screening and diagnostic audio logical assessment.
A research thesis submitted for the degree of Doctor of Philosophy in Audiology in the Faculty of Humanities the University of the Witwatersrand March 2016.
Keywords: Hearing disorders in infants--Diagnosis--South Africa; Newborn infants--Medical examinations--South Africa